The Summons - John Grisham (Berlin Arrow, 2002)
Ray Atlee, a Professor of Law at the University of Virginia, is forty-three and newly single. His father, a very sick old man who lives the life of a recluse in the ancestral home in Clanton, Mississippi, was once a beloved and powerful official who towered over local law and politics for many years. With the end in sight, Judge Atlee issues a summons to Ray to return home to Clanton, to discuss the details of the family estate. Ray reluctantly heads south, but the family meeting does not take place. The Judge dies too soon, and in doing so leaves behind a shocking secret which Ray believes only he knows. Until it becomes clear that someone else knows too...
Keywords: Fiction; Mystery; Thriller; Suspense; Crime; Adult Fiction